2019
DOI: 10.1021/acs.jpclett.9b01953
|View full text |Cite
|
Sign up to set email alerts
|

Water Dramatically Accelerates the Decomposition of α-Hydroxyalkyl-Hydroperoxides in Aerosol Particles

Abstract: α-Hydroxyalkyl-hydroperoxides (α-HHs), from the addition of water to Criegee intermediates in the ozonolysis of olefins, are reactive components of organic aerosols. Assessing the fate of α-HHs in such media requires information on the rates and products of their reactions in aqueous organic matrixes. This information, however, is unavailable due to the lack of analytical techniques for the detection and identification of labile α-HHs. Here, we report the mass spectrometric detection (as Cl– adducts) of the α-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
105
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(107 citation statements)
references
References 66 publications
(144 reference statements)
2
105
0
Order By: Relevance
“…It was found that α-acyloxyalkyl-hydroperoxides decomposed promptly when the pH was larger than 5 in the aqueous phase. The aqueous decomposition of α-hydroxyalkyl-hydroperoxides was also reported to be accelerated by acids, and the rate coefficients of decay increased with decreasing pH (Qiu et al, 2020a). These studies implied that acids, acting as catalysts, promoted the decomposition processes of some compounds in liquid particles and might reduce the quantity of SOAs.…”
Section: Reasons For Different Performances Of Scis Under Different Rh Levelsmentioning
confidence: 90%
“…It was found that α-acyloxyalkyl-hydroperoxides decomposed promptly when the pH was larger than 5 in the aqueous phase. The aqueous decomposition of α-hydroxyalkyl-hydroperoxides was also reported to be accelerated by acids, and the rate coefficients of decay increased with decreasing pH (Qiu et al, 2020a). These studies implied that acids, acting as catalysts, promoted the decomposition processes of some compounds in liquid particles and might reduce the quantity of SOAs.…”
Section: Reasons For Different Performances Of Scis Under Different Rh Levelsmentioning
confidence: 90%
“…Hydrogen peroxide (H 2 O 2 ) is a crucial oxidant in liquid-and aerosol-phase chemistry (Reeves and Penkett, 2003). Additionally, it serves as a temporary reservoir species that cycles and redistributes the HO x radicals (Lee et al, 2000;Tong et al, 2016;Crowley et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…"Educt" factors contain water-labile compounds which are stable under dry conditions but undergo chemical reactions in the presence of water. Likely aqueous-phase reactions are the fragmentation (hydrolysis) of organic (hydro)peroxides Zhao et al, 2018;Qiu et al, 2019) or accretion reactions. Examples for these "educt" factors were SV2, SV4, AV2, and AV4.…”
Section: Interpretation Of the Evolution Of Ncrsmentioning
confidence: 99%